Conceptualizing Service-Learning in Christian Higher Education. Issue 4 (8th August 2018) - Lewing, Morgan
Abstract: Christian higher education is charged with the distinct mission of integrating faith and learning, and course-based service-learning has been identified as a supportive platform for this undertaking. Christian service-learning represents "a teaching and learning strategy that integrates academic instruction, community service, and guided reflection from a Christ-centered, faith-based perspective in order to enhance student learning, to foster civic responsibility, and to develop servant leaders" (Mullen, 2010, p. 164). A large volume of literature pertaining to the theoretical and practical aspects of service-learning courses exists; however, the current literature and corresponding perceptions of best practice may not fully support the distinct nature of service-learning in Christian higher education. Therefore, the purpose of this article is to examine a predominant service-learning typology that dichotomizes traditional and critical service-learning (Mitchell, 2008 ) through the contextualization of faith-based higher education. Then, in an attempt to further elaborate upon Mullen's (2010 ) definition, Morton's (1995 ) typology is recommended to frame Christian service-learning as it acknowledges the validity of multiple paradigms of service-learning (charity, project, and social change) and emphasizes the manner of their implementation (thick versus thin). Micro- and macro-level strategies, based on Morton's (1995 ) typology and subsequent recommendations, are provided to support faculty members and administrators attempting to implement and sustain service-learning at faith-based institutions. Specifically, Christian institutions should prioritize faith-based organizations as core partners, and faculty members should intentionally utilize reflection to integrate faith and learning.